Using a single, high mass resolution mass spectrometry platform to investigate ion suppression effects observed during tissue imaging. (25th March 2014) - Tomlinson, Laura; Fuchser, Jens; Fütterer, Arne; Baumert, Mark; Hassall, David G.; West, Andrew; Marshall, Peter S.
<x xml:space="preserve">Abstract</x> RATIONALE The signal intensity of a given molecule across a tissue section when measured using mass spectrometry imaging (MSI) is prone to changes caused by the molecular heterogeneity across the surface of the tissue. Here we propose a strategy to investigate these effects using electrospray ionization (ESI) and matrix‐assisted laser desorption/ionization (MALDI) on a single high‐resolution mass spectrometry (HRMS) platform. METHODS A rat was administered with a single inhaled dose of a compound and sacrificed 1 h after dosing. Sections were prepared from the excised frozen lung and analysed using MALDI, liquid extraction surface analysis (LESA) nano‐ESI‐MS and nano‐ESI liquid chromatography (LC)/MS. The ESI and MALDI ion sources were mounted either side of the ion transfer system of the same Fourier transform ion cyclotron resonance (FT‐ICR) mass spectrometer. RESULTS MALDI MSI clearly demonstrated widespread distribution of the dosed molecule throughout the lung, with the exception of a non‐lung section of tissue on the same sample surface. Comparison of the lipid signals across the sample indicated a change in signal between the lung and the adipose tissue present on the same section. Use of ESI and MALDI, with and without an internal standard, supported the evaluation of changes in the signal of the dosed molecule across the tissue section. CONCLUSIONS The results demonstrate the successful application of a dual ion source HRMS system to the systematic evaluation of data from MALDI MSI, used to determine the distribution of an inhaled drug in the lung. The system discussed is of great utility in investigating the effects of ion suppression and evaluating the quantitative and qualitative nature of the MSI data. Copyright © 2014 John Wiley & Sons, Ltd.